2004
DOI: 10.1124/jpet.104.074534
|View full text |Cite
|
Sign up to set email alerts
|

Circulation Kinetics and Organ Distribution of Hb-Vesicles Developed as a Red Blood Cell Substitute

Abstract: Phospholipid vesicles encapsulating concentrated human hemoglobin (Hb-vesicles, HbV), also known as liposomes, have a membrane structure similar to that of red blood cells (RBCs). These vesicles circulate in the bloodstream as an oxygen carrier, and their circulatory half-life times (t 1/2 ) and biodistribution are fundamental characteristics required for representation of their efficacy and safety as a RBC substitute. Herein, we report the pharmacokinetics of HbV and empty vesicles (EV) that do not contain Hb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
73
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 74 publications
(73 citation statements)
references
References 31 publications
0
73
0
Order By: Relevance
“…Because this membrane reduces interactions between Hb and NO, adverse effects, such as hypertension and histological damage in myocardial lesions, are not induced, as are found for acellular-type HBOCs (Sakai et al, 2000(Sakai et al, , 2004a. In addition, there are some distinct advantages associated with the membrane structure of HbV as follows; the oxygen affinity (P 50 ) of HbV can be easily regulated by manipulating the content of an allosteric effector such as pyridoxal 5Ј-phosphate , an enhanced lifetime in the blood circulation compared with other types of HBOCs (Sou et al, 2005;Taguchi et al, 2009c), guarantees long-term storage for periods of more than 2 years at room temperature . Moreover, HbV possesses oxygen transport characteristics that are comparable to those of RBCs.…”
Section: Introductionmentioning
confidence: 98%
“…Because this membrane reduces interactions between Hb and NO, adverse effects, such as hypertension and histological damage in myocardial lesions, are not induced, as are found for acellular-type HBOCs (Sakai et al, 2000(Sakai et al, , 2004a. In addition, there are some distinct advantages associated with the membrane structure of HbV as follows; the oxygen affinity (P 50 ) of HbV can be easily regulated by manipulating the content of an allosteric effector such as pyridoxal 5Ј-phosphate , an enhanced lifetime in the blood circulation compared with other types of HBOCs (Sou et al, 2005;Taguchi et al, 2009c), guarantees long-term storage for periods of more than 2 years at room temperature . Moreover, HbV possesses oxygen transport characteristics that are comparable to those of RBCs.…”
Section: Introductionmentioning
confidence: 98%
“…In fact, HbVs have functioned well as blood substitutes in animal models with no noteworthy adverse reactions either in vivo Yoshizu et al, 2004;Cabrales et al, 2005) or in vitro (Ito et al, 2001;Wakamoto et al, 2005;Abe et al, 2006). They also reportedly accumulate in components of the MPS soon after their administration (Sou et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the diameter of HbV liposomes can be tailored to approximately 250 nm, and further modification by PEG leads to an enhanced lifetime in the blood circulation compared with other types of hemoglobin-based oxygen carriers (t 1/2 for cell-free Hb and PEGylated Hb in rats of 1.5 and 10.9 h, respectively) (Goins et al, 1995;Lee et al, 2006) because the encapsulation of Hb completely suppresses renal excretion, although HbVs in the circulation are eventually captured by phagocytes in the mononuclear phagocyte system (MPS) (Sakai et al, 2001). In fact, our group reported that HbV has a long circulation time in blood as an oxygen carrier in mouse, rat, rabbit, and a hemorrhagic shock model rat (Sou et al, 2005;Taguchi et al, 2009a,b). Because of these unique characteristics, such liposomes show an oxygen transport comparable with red blood cells (Sakai et al, 2008) and also show improved survival in hemorrhagic shock animal models (Sakai et al, 2004b(Sakai et al, , 2009.…”
mentioning
confidence: 99%